Optimasi Pemilihan Lokasi Usaha Rental PlayStation Menggunakan Metode Simple Additive Weighting (SAW) di Kabupaten Nganjuk - Sutrisno, Agung Tri (Universitas Multi Data Palembang, 2025)
Business location selection is a key factor in determining the success of an enterprise, particularly for PlayStation rental businesses in developing regions such as Nganjuk Regency. Choosing the right location can enhance competitiveness and profit potential, yet decision-making is often based on subjective intuition. This study aims to develop a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to assist in making objective decisions when selecting strategic business locations. The criteria used include accessibility, population density, rental cost, and level of competition. Data were collected through field surveys and secondary data from the Central Bureau of Statistics. The system implementation results indicate that shopping center areas received the highest preference scores, followed by areas near campuses and city centers. The SAW-based DSS has proven effective in improving the objectivity, efficiency, and accuracy of business location selection. Furthermore, this method holds potential for broader application in various location-based business types.